A STUDIO-BASED EXPLORATION OF MATERIAL INNOVATION IN HANDLOOM WEAVING - Edward Apau; Morrison Appiagyei Boadi; Reindolf Amponsah Monnie; Bright Kofi Koseme (ARTISTIC : International Journal of Creation and Innovation, 2026)
Frequent warp yarn breakages continue to reduce the efficiency of handloom weaving, especially when using traditional spun yarns like cotton and polyester. This study explores the possibility of using nylon threads as unconventional yarns for hand weaving to overcome this issue. A studio-based, practice-led experimental design was employed, using nylon threads, commonly found in non-textile applications, as both warp and weft materials to evaluate their performance under real weaving conditions. The results show that nylon’s high tensile strength and abrasion resistance allowed it to function effectively as warp yarns, preventing breakages during weaving and creating tight, durable fabrics suitable for non-clothing uses such as upholstery and interior textiles. However, its slippery texture affected weft performance, necessitating modifications such as the use of open reeds and adjusted dent densities. The study demonstrates that nylon threads can be successfully adapted for handloom production as tough warp materials, providing an innovative alternative that reduces production inefficiencies. By reinterpreting a non-traditional material through studio-based experimentation, the research contributes to sustainable textile design and underlines the importance of material innovation in advancing modern handloom practices.